THE EFFECTS OF GENDER ON THE UNDERGRADUATING STUDENTS’ ENTREPRENEURIAL INTENTION - T Santhanamery; Dalili Izni Shafie; Saw-Imm Song; Nor Aminin Khalid, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The purpose of this research paper is to investigate the effect of gender on students’ entrepreneurial intention (EI) as well as the determinants of the EI. This research integrated the Theory of Planned Behaviour and Integrated Behavioural Model in adapting the variables in determining the intention. This paper has two objectives, initially it aims to contribute to the literature on EI by integrating the Theory of Planned Behavior (TBP) and Integrated Behavior Model (IBM) to the Malaysian settings. Then, it investigated the effect of gender on Attitude, Perceived Behavioral Control (PBC) and Self Efficacy (SE) towards behavior on students’ entrepreneurial intention in the future. The sample consists of 429 UiTM students who have taken the entrepreneurship course. The data was analyzed using Smart PLS 3.3.7. The findings of this study revealed that gender has no significant relationship with students’ EI, attitude, PBC and SE towards students’ entrepreneurial intention. In terms of the integrated model, the findings discovered that attitude and PBC have a statistically significant relationship with EI. However, SE does not have a significant relationship towards EI. The findings will help the policymakers or the higher education institutes in developing a suitable policy and program in promoting entrepreneurship to the university graduates at the national level.